The formal and legal process of conducting an independent risk management assessment in rail transport - Magdalena Garlikowska (Przegląd Komunikacyjny)
Abstract: Striving to increase the safety of rail transport is a priority for the European Union and all rail entities. One of the areas of this safety is risk management in connection with changes introduced to the railway system. Every entity operating on the railway market is obliged to do so. The article discusses the risk management process carried out by the Applicant - from the assessment of the significance of the change, through the risk analysis, to the submission of documents to the inspection (assessment) unit for independent assessment of the correctness of the risk management carried out by the Applicant. Keywords: Independent assessment; Security; Risk assessment; Risk management